The Study of Simplification and Explicitation Techniques in Khaled Hosseini's “A Thousand Splendid Suns” - Reza Kafipour (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2016)
Teaching and learning strategies help facilitate teaching and learning. Among them, simplification and explicitation strategies are those which help transferring the meaning to the learners and readers of a translated text. The aim of this study was to investigate explicitation and simplification in Persian translation of novel of Khaled Hosseini's “A Thousand Splendid Suns”. The study also attempted to find out frequencies of simplification and explicitation techniques used by the translators in translating the novel. To do so, 359 sentences out of 6000 sentences in original text were selected by systematic random sampling procedure. Then the percentage and total sums of each one of the strategies were calculated. The result showed that both translators used simplification and explicitation techniques significantly in their translation whereas Saadvandian, the first translator, significantly applied more simplification techniques in comparison with Ghabrai, the second translator. However, no significant difference was found between translators in the application of explicitation techniques. The study implies that these two translation strategies were fully familiar for the translators as both translators used them significantly to make the translation more understandable to the readers.